Voci : Encounters with Italian. - Bosco, Frederick J. (Toronto Italian studies., 1996)
The aim of Voci is to promote creative expression in Italian. Through the combination of readings and the exercises students learn about Italian culture, history, and language while they expand and develop their language skills.